The carpet industry and its impact on the Iranian economy During the Qajar period (1796-1899) - Abdulali, Assistant prof .Dr.Nahla Naeem (Thi Qar Arts Journal, 2024)
The topic of this research is considered one of the important historical subjects; its significance lies in the fact that carpet weaving is an industry that enjoys a special status compared to common industries, crafts, and known artistic specializations. The use of various artistic decorations and patterns on carpets has added charm and beauty to this industry, making it an active attraction for European tourists and foreign investors at the time.In our research, we have chosen to address the development of this industry and how it transformed from a craft practiced in homes and villages to an important urban industry, whose products formed the largest portion of the country’s exports. We shed light on the role of kings in establishing and developing carpet weaving workshops, especially those established in royal palaces and mosques. We also highlighted the contribution of the wealthy and courtiers in this field, and the extent of the connection that art of painting had with this industry, after weavers introduced silk flowers they wove using hand looms. In addition, we focused on the intellectual and cultural atmosphere that surrounded the artists during that era, their influence by Western culture, and its reflection on the carpet industry in particular, and on architecture and other arts in general. Thus, our research includes a brief study of the topic, with an analysis of some related details, relying on numerous Persian sources.